A Survey study on design procedure of Seismic Base Isolation Systems - Hossein Shakeri Soleimanloo (Journal of Applied Sciences and Environmental Management)
Adding shear walls or braced frames can decrease the potential damage caused by earthquakes.We can isolate the structures from the ground using the Seismic Base Isolation Systems that is flexible approach to decrease the potential damage. In this research we present information on the design procedure of seismic base isolationsystems. In addition, we analyze the seismic responses of isolated structures. The seismic isolation includes the installation of mechanisms, which decouple the structure. This decoupling is achieved by increasing the horizontalflexibility of the system, together with providing appropriate damping. In this research we use some codes forthe design examples of elastomeric bearings. Experimental results indicate the effectiveness our approach.